Isothermal sintering kinetic of 3YTZ and 8YSZ: Cation diffusion - Suarez, Gustavo (2013)
We have studied the sintering kinetic of 3 and 8 mol% of yttria stabilized zirconia under isothermal conditions. Sintering was performed in the temperature range between 1200 and 1450 °C. The sintering kinetic process was followed by measuring density as a function of sintering time. A model was applied to the first stage of densification. Sintering obeys to the grain boundary diffusion mechanism for both materials. It was possible to calculate the activation energy as well as the diffusion coefficients. 887 and 731 kJ mol−1 were the activation energies for the initial stage of sintering for 3YTZ and 8YSZ respectively. Finally the diffusion activation energy was estimated for both materials. The diffusion coefficients were also estimated at 1400 °C in 4.05×10−14 and 6.00×10−11 cm2 s−1 for tetragonal and cubic zirconia respectively. The obtained results support the observations of a faster densification for 8YSZ.